Distribution and Establishment of the Lone Star Tick in Connecticut and Implications for Range Expansion and Public Health. Issue 6 (25th July 2018) - Stafford, Kirby C; Molaei, Goudarz; Little, Eliza A H; Paddock, Christopher D; Karpathy, Sandor E; Labonte, Andrew M
Abstract: In the United States, the lone star tick, Amblyomma americanum (L.) (Acari: Ixodidae), is an aggressive southeastern species whose range has reportedly been steadily expanding northward. The number of A. americanum specimens submitted to the Tick Testing Laboratory (TTL) at the Connecticut Agricultural Experiment Station (CAES) increased by 58% from the period of 1996–2006 ( n = 488) to 2007–2017 ( n = 773), mainly from Fairfield County in the southwestern corner of the state. The greatest numbers of A. americanum submissions to the CAES-TTL were from the City of Norwalk and a few adjacent municipalities. We also report the discovery of a large infestation of adult and nymphal lone star ticks detected on a dead male white-tailed deer, Odocoileus virginianus (Zimmerman) (Artiodactyla: Cervidae), on Manresa Island, Norwalk, in June 2017, indicating a long established, undetected population along the southwestern coast. A sample of nymphal and adult host-seeking A. americanum collected July 2017 from Manresa Island were tested and a proportion were positive for Ehrlichia chaffeensis, Ehrlichia ewingii, and Anaplasma phagocytophilum . The A. americanum tick and its associated disease pathogens are expected to become an increasing public health concern in southern New England.